Investigation on tensile properties and analysis of wear property of glass fiber-epoxy-nanoclay ternary nanocomposite using response surface methodology. Issue 1 (1st January 2021) - Hiremath, Pavan; Kini U, Achutha; Shettar, Manjunath; Sharma, Sathyashankara; P K, Jayashree
Abstract: The current study's objective is to investigate the impact of nanoclay on the tensile and wear properties of glass fiber-epoxy-nanoclay ternary nanocomposite. Three types of composites are produced by hand lay-up process and compression molding. Tensile and wear tests are executed according to ASTM standards. The findings disclosed that nanoclay enhanced the tensile properties of glass fiber-epoxy-nanoclay ternary nanocomposite. The causes for the failure under tensile load are revealed by SEM micrographs. Response surface methodology (RSM) is applied to analyse the wear loss of nanocomposite. The "Box–Behnken method" is employed for experimental design to establish the main and interaction effects among factors comprising nanoclay (NC), load, and sliding distance in three levels (0, 2, and 4 wt.% for nanoclay; 1, 3, and 5 kg for load; and 300, 600, and 900 rpm for sliding distance). The RSM offers a strong confidence model for each response. Also, RSM models are often used to estimate the optimum case with the minimum mass loss. The optimum results are estimated for the combination of 4 wt.% nanoclay, 1 kg load, and 300 rpm for sliding distance. Experimental test results revealed an agreement with the predicted values.